Pendidikan Islam Dari Sudut Pandang Kehidupan Manusia - Tria Mauliza; Aziche Calista Mayo; Cameilah Az-zahra; Tsabita Helwena; Wismanto Wismanto (STIKes Ibnu Sina Ajibarang, 2024)
Islam uses the teachings of the Koran and Hadith and enriches them through the interpretations and tawir of scholars who provide clear and in-depth explanations of various controversies that exist in the world of education. Islam is a universal, holistic and comprehensive system of life that establishes the order of human life as a whole. As a guide to life, Islam regulates everything related to life, from the simplest things to the most complicated. Both in the fields of politics, economics, education, arts, social culture and other aspects. Islam means true faith and regulates matters related to the economy. If a country's economy (national economy) uses the Al-Quran and Hadith as the basis for its implementation, of course the national economy will run well and run in line with the rules. However, in fact, not all Islamic countries in the world have implemented this basis. Islam is the spirit of a lifestyle whose teachings demand salvation in the world and the hereafter, even in human civilization in the form of rahmatan lil`alamin.